A multimodal analysis of cover stories on mobile phones: An ideational perspective / Salveen Kaur Gill A/P Sakdev Singh - Salveen Kaur Gill, Sakdev Singh (2015)
Cover stories generally contain magazine articles which focuses the subject matter on the cover. The interest of this study is on new products specifically mobile phones presented in “Mobile World” magazine as nowadays, there is a competition in selling mobile phones (Ni’Mah, 2012). Therefore, the study will explain on how linguistic and visual features of cover stories could be deciphered as an adverting message through investigating linguistic and visual representation used in magazine cover stories. The data in this study are taken from a magazine of cellular consumer’s guidance, namely “Mobile World” magazine published by One World Solutions Sdn Bhd. This study attempts to explore cover stories in the first six months of 2013 but only those which focus on Mobile phone rather than Tablet or other devices. To fulfil the aim of this study, first, the linguistic text of the cover stories of the magazines was analysed in terms of process, participant and circumstance through utilizing Halliday’s (2004) transitivity system. In the next step, the visual components of cover stories of the magazines were selected to be examined according to Kress and van Leeuwen’s (2006) narrative and conceptual representation analysis to differentiate between the visual elements provided in cover stories. The findings found out that material and relational processes are commonly used as these emphasise on the capability and functions of the mobile phone advertised. As such, the highlighted features would draw potential buyers to consider buying the new phones. Similarly, visual findings on Action and Reaction processes were extensively seen in the images of the cover stories. With that, the different life experience of the consumers when using or owning is identified and interaction between the participants of the images plays an important role in consumerism marketing.